2014
DOI: 10.1186/1472-6882-14-100
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia capillaris inhibits atopic dermatitis-like skin lesions in Dermatophagoides farinae-sensitized Nc/Nga mice

Abstract: BackgroundArtemisia capillaries Thunb. (AC) has been used to treat inflammatory and hepatic disorders such as hepatic injury, hepatic fibrosis and hepatitis. However, the efficacy of AC against atopic dermatitis (AD), an inflammatory disease, has not been examined. In the present study, AC was evaluated for anti-inflammatory and anti-AD effects using both in vitro and in vivo systems.MethodsThe contents of six compounds (chlorogenic acid, caffeic acid, isochlorogenic acid A, hyperoside, isoquercitrin and scopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…YC mainly contains phenolic acids, flavonoids, and coumarins [4][5][6][7]. And phenolic acids are proved in previous studies to have various biological functions, including antioxidant [8,9], anti-inflammatory [10], antibacterial [11], cytoprotective [9], hepatoprotective [12,13], and anti-osteoporosis [14,15] effects.…”
Section: Introductionmentioning
confidence: 99%
“…YC mainly contains phenolic acids, flavonoids, and coumarins [4][5][6][7]. And phenolic acids are proved in previous studies to have various biological functions, including antioxidant [8,9], anti-inflammatory [10], antibacterial [11], cytoprotective [9], hepatoprotective [12,13], and anti-osteoporosis [14,15] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia capillaris (AC) Thunberg has been used as food additives and traditional phytomedicines. The major components of AC are chlorogenic acids, coumarins, and flavonoids (Ha, Lee, Seo, et al, ; Okuno, Uchida, Nakamura, & Sakurawi, ). AC exhibited therapeutic potentials for the treatment of cancer, hepatitis, inflammation, malaria, obesity, and microbial infections (Aniya, Shimabukuro, Shimoji, et al, ; Cha, Moon, Kim, Cha, & Lee, ; Hong, Hwang, Kim, Jeong, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the application of the extract of AC (ACE) can reduce interleukin‐1beta (IL‐1β) and interferon‐gamma‐induced nitric oxide (NO) production, which may be correlated well with the reduced expression levels of the inducible nitric oxide synthase (iNOS) mRNA and protein (Kim, Kwon, Han, et al, ). Related to the treatment of skin disorders, AC inhibited atopic dermatitis‐like skin lesions in Dermatophagoides farinae ‐sensitized Nc/Nga mice (Ha et al, ). The pharmacological active components were extracted with ethanol from the whole part of AC in this study and the antipsoriatic potentials of ACE were first, to the best of our knowledge, demonstrated in imiquimod (IMQ)‐induced psoriasis‐like mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of constituents including p -hydroxyacetophenone, β -sitosterol, scoparone, cirsimaritin, quercetin, arcapillin, capillin, 6,7-dimethylesculetin, 6,7-dimethoxycoumarin, capillone, capillarin, 4′-methyl capillarisin, cirsilineol, cirsimaritin, and capillarisin from A. capillaris have been shown to have antihepatofibrotic, anti-inflammatory, choleretic, and hepatoprotective activities [ 6 10 ]. Furthermore, more diverse pharmacological properties of A. capillaris have been studied in areas such as lipoapoptosis, obesity, skin cancer, antibacterial activities, and atopic dermatitis, as well as liver protection [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%